Continuous bilateral erector spinae plane analgesic block for an adolescent with Nuss repair of pectus excavatum - Ayòtúndé B. Fadayomi; Asmerom Adhanom; Patricia Amelin; Gustavo G. Angaramo (Elsevier, 2020)
Thoracic epidural analgesia has been proven to be an effective method for pain management following Pectus excavatum repair. However, because of the accompanying thoracic spinal deformities, thoracic epidural analgesia may not always be a feasible option in all cases. If ineffective, there could be increased opioid administration in order to adequately manage any post operative pain. Studies have shown that early exposure of adolescents to opioids is associated with increased risk of persistent opioid use. This is because adolescents have larger reward centers and underdeveloped prefrontal cortex, hence an immature inhibitory system. An alternative regional technique for post operative pain management in these patients is thus valuable. Erector spinae plane (ESP) block has been explored and found to be a useful alternative for pain management in this group of patients. Although there are a few case reports showing the effectiveness of ESP blocks in Ravitch repair, we present, for the first time, the effectiveness of ESP in Nuss repair. Keywords: Erector spinae block, Nuss repair, Analgesic block